Grammatical Error Analysis in English Education Students' Recount Text - Astuti, Peni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2022)
Learning English is becoming increasingly important nowadays because we know that English is one of the international languages used to communicate around the world. In Indonesia, English is taught as a foreign language. Learning a different language may be difficult because the target language contains elements other than the mother tongue. These differences may lead students to make some errors in their use. The ability to write a story, which is a communicative skill, requires another competency. The past tense should be learned for being able to write a recount text properly. First, it describes the grammatical errors in the recount texts made by the first-year students of the English Education Department of Faletehan University. In this study, the researcher used the qualitative approach in which the data were obtained from the students’ recount handwriting. These writings were later analysed. The grammatical errors were classified into seven groups; errors in producing verb group, errors in subject-verb agreement, errors in the use of articles, errors in prepositions, errors in noun pluralisation, errors in pronouns and errors in pronouns, and errors in the use of conjunctions. The study sample was 688 sentences made by 10 students in the second semester of the English Education Department of Faletehan University in the academic year 2020/2021, taken by cluster random sampling technique. The data were collected using two instruments: a writing test to find the students’ grammatical errors. Data on the students’ errors were analysed by using descriptive statistics. The result of the study showed that the students made 235 errors classified into seven types of errors which consisted of 153 or 65% errors in using verb forms, 3 or 1.3% errors in the agreement between subject and verb, 10 or 4.3% errors in the use of an article, 30 or 12.8% errors in the use of preposition, 12 or 5.1% errors in pluralisation, 23 or 9.8% errors in the use of the pronoun, and 4 or 1.7% errors in the use of a conjunction. The students' top three frequent grammatical errors were errors in using verb forms, errors in the agreement between subject and verb, and errors in using the article. It is suggested that students still need more practice regarding verbal forms as they were the core knowledge required to relate their past experiences.